Normative Influences on Network Structure in the Evolution of the Children's Rights NGO Network, 1977-2004. (February 2015) - Margolin, Drew B.; Shen, Cuihua; Lee, Seungyoon; Weber, Matthew S.; Fulk, Janet; Monge, Peter
This study examines the impact of legitimacy on the dynamics of interorganizational networks within the nongovernmental organizations' children's rights community. The 27-year period of analysis included a critical community event: the ratification of the United Nations Convention on the Rights of the Child (UNCRC). Building on theories of organizational evolution, hypotheses proposed that (1) ratification of the UNCRC served to codify and more broadly communicate the legitimate norms of the community, and (2) dissemination of normative information made it easier (a) for less experienced organizations to form and maintain partnerships, and (b) for organizations to form partnerships without reference to shared third-party contacts or dominant organizations. Data analysis via a longitudinal network model supported the hypotheses. Further investigation via an event history analysis suggested that these effects were largely confined to links among organizations in the children's rights community and not to links made by these organizations to more general others.